Effect of lognormal particle size distributions of non-spherical particles on hopper discharge characteristics - Zhao, Ya (2022)
This study focusses on the hopper discharge characteristics of lognormal particle size distributions (PSDs) of non-spherical particles (namely, ellipsoids, cylinders and cuboids). Discrete element method is employed to understand the coupled effects of sphericity and lognormal PSD width. The results reveal that: (i) the ellipsoids have the most similar discharge behaviors with the spheres, but the differences increase as the PSD width increases; (ii) the packing density in the hopper increases as PSD width increases and particle sphericity decreases; (iii) regardless of sphericity, the discharge rate decreases and the jamming probability increases as the PSD width increases; (iv) for the same PSD width, the jamming probability is the greatest for cuboids and least for the ellipsoids; and (v) the lower-sphericity cylinder and cuboid have some residual particles left in the hopper upon complete discharge, and the number of residues is greater and increases with PSD width for the latter. The results provide new insights regarding the behavior of wide PSDs of non-spherical particles in the hopper, highlighting the non-negligible impact of the coupled effect of PSD and particle non-sphericity.